2022
DOI: 10.1039/d1ma01169c
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine adjuvant platform and fluorescence imaging of amphiphilic γ-PGA-IMQ-LA-FL conjugates

Abstract: Adjuvants have proven to be integral components in most vaccines for promoting appropriate immune responses at both innate and adaptive levels. Imiquimod (IMQ, R837), an agonist for Toll-like receptors 7...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Undoubtedly, the safety issue of IMQ-Chol is a prerequisite for its biomedical applications as a good adjuvant. However, our previous research indicated that pristine IMQ was found to be more cytotoxic and triggered different degrees of toxic side effects after subcutaneous injection in mice. Considering animal ethics and its poor solubility, we did not use IMQ as a control in our following experiment.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Undoubtedly, the safety issue of IMQ-Chol is a prerequisite for its biomedical applications as a good adjuvant. However, our previous research indicated that pristine IMQ was found to be more cytotoxic and triggered different degrees of toxic side effects after subcutaneous injection in mice. Considering animal ethics and its poor solubility, we did not use IMQ as a control in our following experiment.…”
Section: Resultsmentioning
confidence: 94%
“…FMDV-specific IgG (Lanzhou Shouyan Biotechnology, Co., Ltd.) and subtypes (IgG1, IgG2a) in the serum of the immunized mice were detected by mouse IgG1 and IgG2a ELISA kit (Multi Sciences (LIANKE) Biotech, Co., Ltd.) 2−12 weeks after immunization according to a previous study. 15 The absorbance was calculated at 450 nm using a microplate reader (Bio-Rad), and all samples were measured in quadruplicate.…”
Section: Animals and Cellsmentioning
confidence: 99%
See 2 more Smart Citations